A case in which bladder cancer invaded the ureteral orifice and was resected via photodynamic diagnosis‐assisted transurethral resection involving orally administered 5‐aminolevulinic acid. Issue 6 (13th September 2019) - Watanabe, Keitaro; Shirotake, Suguru; Umezawa, Yuta; Takahashi, Takayuki; Yamanaka, Takeshi; L Santo, Noriaki; Okabe, Takashi; Kaneko, Gou; Sano, Katsuhiro; Yasuda, Masanori; Kanao, Kent; Oyama, Masafumi; et al.
Abstract : Introduction: Transurethral resection of bladder tumor is widely used in combination with photodynamic diagnosis to treat non‐muscle invasive bladder cancer. We experienced an intriguing case, in which bladder cancer infiltrated into the right ureteral orifice and was resected via photodynamic diagnosis‐assisted transurethral resection involving the oral administration of 5‐aminolevulinic acid. Case presentation: This case was a 71‐year‐old Japanese man. He was diagnosed with bladder carcinoma, which had infiltrated into the right ureter (clinical classification: T1, N0, M0). He underwent transurethral resection involving the oral administration of 5‐aminolevulinic acid. We successfully resected the tumor in the ureteral orifice, which was accomplished by resecting the ureteral orifice until the non‐luminescent lumen was exposed. After the surgery, to prevent recurrence, Bacillus Calmette–Guérin was administered intravesically after right ureteral stent placement. Conclusion: Photodynamic diagnosis‐assisted transurethral resection involving the oral administration of 5‐aminolevulinic acid has the potential to treat ureteral tumors derived from bladder tumors.